(untitled) (Journal of Engineering, 2011)
This paper provides the result of an investigation to use of crushed clay brick as aggregates in producing concrete. Eight different crushed clay brick aggregate concretes were used in this investigation. Compressive strength, splitting tensile strength and pulse velocity of crushed clay brick aggregates concrete were determined and compare to natural aggregate concrete. The compressive strength of crushed clay brick aggregates concretes were always lower than the compressive strength of natural aggregates concrete regardless the age of concrete, but the crushed clay brick aggregates concrete showed better performance as the age of concrete increases and average reduction in compressive strength were 33.5% at the age of 7 days but it becomes only 20% at the age of 56 days compared to natural aggregates concrete. The splitting tensile strength of crushed clay brick aggregates concrete were always lower than natural aggregate concrete, the reduction in splitting tensile strength of crushed clay brick aggregates concrete is ranging between 11 and 26% with an average reduction of about 18.5% compared to natural aggregates concrete. The pulse velocity of crushed clay brick aggregates concrete were also lower than natural aggregates concrete, the reduction in pulse velocity of crashed clay brick aggregates concrete is ranging between 6 and 22% with an average reduction of about 14% compared to natural aggregates concrete.